2014
DOI: 10.1159/000360072
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age-Specific Reference Ranges of Hepcidin in Cord Blood

Abstract: Background: Iron deficiency (ID) contributes to anaemia of prematurity, and hence the reliable assessment of iron nutrition status appears to be mandatory. Objective: To establish gestational age (GA)-specific reference ranges for hepcidin concentrations in cord blood [Hep(CB)] of preterm and term infants and to identify pre- and perinatal confounding factors. Methods: This is a prospective observational study including 221 infants (GA at birth: 24-42 weeks). Hep(CB) along with complete b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
7
24
3
Order By: Relevance
“…All term neonates in this study had detectable hepcidin at birth and mean concentrations observed were similar to those reported among term neonates using the same hepcidin assay (30). Hepcidin concentrations were higher in newborns born to mothers with longer durations of labor.…”
Section: Discussionsupporting
confidence: 84%
“…All term neonates in this study had detectable hepcidin at birth and mean concentrations observed were similar to those reported among term neonates using the same hepcidin assay (30). Hepcidin concentrations were higher in newborns born to mothers with longer durations of labor.…”
Section: Discussionsupporting
confidence: 84%
“…We also recognize that the overall distribution of cord hepcidin levels were low compared with reference standards measured in European neonates, possibly reflecting differences in dietary iron and genetics. 41 In conclusion, the results of this study highlight the likely involvement of hepcidin in the maintenance of iron homeostasis at the maternal-fetal interface and suggest that measuring hepcidin during infancy may provide an early indication of a child's future susceptibility to anemia and ironrequiring pathogens.…”
mentioning
confidence: 58%
“…Consistent with prior investigations, cord hepcidin had a positive, dose-response relationship with cord ferritin . 40,41 The positive association between cord hepcidin and placental levels of soluble transferrin receptor was initially unexpected given earlier findings of an inverse association from the transgenic Thep27 mouse line, in which fetal hepcidin from constitutively hepcidin-expressing offspring was shown to downregulate placental transferrin receptor mRNA. 42 However, further investigation showed that high (i.e., above median) placental levels of soluble transferrin receptor were coincident with lowered maternal ferritin (P = 0.019, Wilcoxon rank-sum test) and normal cord ferritin (P = 0.48, Wilcoxon rank sum test), suggesting that the elevated placental soluble transferrin receptor could be, as previously described, a compensatory mechanism by which the placentas of iron-depleted mothers may enhance transfer of iron to the fetuses despite maternal iron deficiency, thereby mediating conflicting maternal-fetal iron demands.…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation of hepcidin levels in neonates, Lorenz et al [11] identified higher levels of hepcidin in the umbilical cord blood of infants born at term compared to that of preterm infants. However, Lorenz et al did not include hypoxic or inflammatory factors as predictor variables in their multiple regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, only a few studies have investigated the association between hepcidin levels and these conditions in premature infants who are often exposed to various perinatal factors associated with inflammation and hypoxia [11,12]. Moreover, the influence of prematurity on hepcidin levels remains unclear.…”
Section: Introductionmentioning
confidence: 99%